2012
DOI: 10.3233/jad-2012-120007
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive Alzheimer's Disease: A Multicenter Update

Abstract: The objective was to characterize a rapidly progressive subtype of Alzheimer's disease (rpAD). Multicenter (France, Germany, Japan, Spain) retrospective analyses of neuropathologically confirmed rpAD cases initially classified as prion disease due to their clinical phenotype were performed. Genetic properties, cerebrospinal fluid biomarkers, neuropathology, and clinical features were examined. Eighty-nine patients were included (median survival 10 months). APOE and PRNP codon 129 genotype distribution parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 18 publications
3
54
0
5
Order By: Relevance
“…Two distinct subtypes of dementia progression have been identified, especially in AD [47,54,58], cases having either a very short (median survival 10 months) or a significantly longer survival and which may reflect education level [18,21]. Short survival cases were also evident in the present sample of FTLD-TDP, nine cases surviving for two years or less.…”
Section: Discussionmentioning
confidence: 52%
“…Two distinct subtypes of dementia progression have been identified, especially in AD [47,54,58], cases having either a very short (median survival 10 months) or a significantly longer survival and which may reflect education level [18,21]. Short survival cases were also evident in the present sample of FTLD-TDP, nine cases surviving for two years or less.…”
Section: Discussionmentioning
confidence: 52%
“…Recently it has been observed that patients suffering from rpAD present highly increased ptau levels in the CSF [146] when compared to controls and classical AD patients. Since it is estimated that rpAD may be accounting for 10-30% of all AD cases, it is urgently needed to establish if lack of disease stratification may lead to misinterpretation of p-tau analysis between rapidly progressive and classical AD forms.…”
Section: Phospho-taumentioning
confidence: 99%
“…In a rapidly progressing form of AD that clinically may mimic CJD, the genetic profile (absence of ApoE ε4 homozygenity and biomarkers) differs from classical AD, suggesting that it might represent a distinct subtype of AD [209].…”
Section: Rapidly Progressive and Early Onset Dementiasmentioning
confidence: 99%